(untitled) (Third Sector Social Economic Review, 2022)
Increasing attention to sustainability issues is forcing companies to shift the focus of their logistics operations from cost minimization to simultaneous cost and environmental impact minimization. Although conventional vehicles are still predominantly preferred in transportation, it can be mentioned that there is an increasing trend in the use of hybrid and electric vehicles due to environmental legislations and environmentally sensitive consumers. However, these vehicles can be adversely affected by unforeseen events during the transportation process (e.g., traffic jam) in a dynamic environment. This article proposes a mixed integer linear programming based solution algorithm for a sustainable dynamic vehicle routing problem. The importance of considering the dynamic environment for an electric vehicle routing problem has been demonstrated through numerical analysis. According to the results, it has been observed that the battery constraints that come with the use of electric vehicles are seriously affected by the dynamic environment and vehicles below a certain battery capacity cannot meet the needs of all customers.